Mechatronics dynamics of electromechanical and Piezoelectric systems - Preumont, André (Solid mechanics and its applications, 2006)
This volume treats Lagrange's equations for electromechanical systems, including piezoelectric tranducers and selected applications. It is essentially an extension to piezoelectric systems of the work by Crandall et al.: Dynamcs of Mechanical and Electromechanical Sysyems, McGraw-Hill, published in 1968. The first three chapters contain classical meterial based on this and other well-known standard texts in the field, such as Methods of Analltical Dynamics by L. Meirovitch, McGraw-Hill, 1970. Some applications are new (e.g. geophone). Chapters 4 to 6 consist of new material which has not been published in a mongraph before. They deal with piezoelectric systems in a unified way, starting from a lagrangian approach.